"Bara en fot och en känga": Vargdödade barn i Finland i folktradition och mediematerial - Strandén-Backa, Sofie (Budkavlen, 2020)
‘A foot and a boot’. Narratives about children killed by wolves in Finnish folk tradition and media material Sofie Strandén-Backa Keywords: wolf attacks in Finland 1880–1881, children, living tradition, mass and social media The article focuses on narratives about children and wolves, and the material consists of different texts that deal with children who have been killed by wolves in Finland in earlier times. The particular events in question are a series of well-known and documented wolf attacks on children in the Turku region during 1880 and 1881. Older newspaper articles, as well as contemporary texts, are analysed. One aim of the study is to investigate what is set in motion when the relationship between wolves and children is discussed and which underlying patterns emerge as part of that discussion. Another aim is to allow for narrative elements to create a base for discourse about the dangerous wolf. The analysis covers peoples’ comments on websites where the discourse is both defended and challenged and where negotiations about the prerogatives of the animal are made visible. Ever-returning narratives about the dangerous wolf are part of a legend process, where one goal is to convince the audience of the truth of the stories. One way of doing so, throughout the years, has been to present what could be called ‘the bloody list’, a list that consists of the name and age of the dead children, the circumstances under which they were killed and what was left of their bodies. In the stories, there was no way to protect the children, and there is nothing the parents could have done once the wolf got hold of their child. The message in these stories from the 1880s is that there is no rescue from the wolf. This message is passed down to parents and further to the children of today, creating a child-eating beast of (every) wolf. Another goal is to keep the stories alive for future generations, since the events are viewed as so important that they are not to be forgotten. The stories have a somewhat emblematic character, since they reflect an original myth about the genesis of modern Finland, freed from untamed nature and the chaos of wolves.